NANOPARTICLE-BASED BIOMARKERS FOR EARLY DIAGNOSIS AND PROGNOSIS OF CANCER - Omar Khan; Amir Raza; Dito Anurogo (Journal of Biomedical and Techno Nanomaterials, 2026)
Nanoparticle-based biomarkers have shown great potential for the early diagnosis and prognosis of cancer, offering enhanced sensitivity and specificity compared to traditional diagnostic methods. The use of nanoparticles as carriers for biomolecules enables the detection of low-abundance biomarkers in the bloodstream, facilitating the identification of cancer at its early stages when treatment options are more effective. This study investigates the development and application of nanoparticle-based biomarkers for improving cancer detection and prognosis. The primary objective of this research is to evaluate the diagnostic and prognostic capabilities of nanoparticle-functionalized biomarkers in detecting various types of cancer. In vitro assays, animal models, and clinical sample analysis were employed to assess the binding affinity, detection sensitivity, and prognostic value of these biomarkers. The results indicate that nanoparticle-based biomarkers significantly enhance the detection of specific cancer markers, achieving high sensitivity and specificity, particularly in detecting early-stage cancer. Additionally, these biomarkers show promise in predicting tumor progression and patient outcomes. In conclusion, nanoparticle-based biomarkers represent a promising tool for the early diagnosis and prognosis of cancer, with the potential to improve clinical decision-making and treatment outcomes by enabling timely interventions.